2009
DOI: 10.4161/pri.3.2.9135
|View full text |Cite
|
Sign up to set email alerts
|

The cellular prion protein and its role in Alzheimer disease

Abstract: The cellular prion protein (PrP C ) is a membrane-bound glycoprotein especially abundant in the central nervous system (CNS). The scrapie prion protein (PrP Sc, also termed prions) is responsible of transmissible spongiform encephalopathies (TSE), a group of neurodegenerative diseases which affect humans and other mammal species, although the presence of PrP C is needed for the establishment and further evolution of prions.The present work compares the expression and localization of PrP C between healthy human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
3
20
1
Order By: Relevance
“…Our results appear to be in general disagreement with the central topic of recently published studies by Velayos and co-workers 29 which indicated a tendency for lower steady state PrP C levels in the brains of AD patients compared to controls, 29 especially in the hippocampus, an outcome apparently inconsistent with previous reports of increased PrP C immunoreactivity in the temporal cortex, hippocampus (CA2) and subiculum in AD patients compared to controls. 30 Although not discussed in the context of their data, the report of Velayos and co-workers was significant in light of recent studies implicating PrP C as a major receptor that mediates the deleterious effects of oligomeric Aβ1-42 on synaptic function.…”
Section: Methodscontrasting
confidence: 99%
“…Our results appear to be in general disagreement with the central topic of recently published studies by Velayos and co-workers 29 which indicated a tendency for lower steady state PrP C levels in the brains of AD patients compared to controls, 29 especially in the hippocampus, an outcome apparently inconsistent with previous reports of increased PrP C immunoreactivity in the temporal cortex, hippocampus (CA2) and subiculum in AD patients compared to controls. 30 Although not discussed in the context of their data, the report of Velayos and co-workers was significant in light of recent studies implicating PrP C as a major receptor that mediates the deleterious effects of oligomeric Aβ1-42 on synaptic function.…”
Section: Methodscontrasting
confidence: 99%
“…Another finding which we have come across is that in mice the expression of the non-glycosylated band becomes more pronounced with age, above all in female mice which is in agreement with our previous findings [30]. One can probably say, by extrapolation, and based on previous findings of Velayos et al [30], that in humans, and more so in women, the greater propensity for Alzheimer's disease and the cognitive symptoms specific to the elderly may be related to the level of non-glycosylated PrPC, all this taken together with the above considerations, with regard to the frontal cortex.…”
Section: Discussionsupporting
confidence: 93%
“…One can probably say, by extrapolation, and based on previous findings of Velayos et al [30], that in humans, and more so in women, the greater propensity for Alzheimer's disease and the cognitive symptoms specific to the elderly may be related to the level of non-glycosylated PrPC, all this taken together with the above considerations, with regard to the frontal cortex. On the other hand, the incubation period of the prionopathies is shorter in female mice than in males [37].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…38 (Whitehouse and Hooper NM, unpublished). A recent brief report 39 that showed a decrease of PrP C in the hippocampus, frontal cortex and temporal cortex in AD would also appear to support this. However, the number of cases (two AD and three controls) was too small for statistical analysis and whether the AD cases were sporadic and appropriately age matched with the controls not reported.…”
Section: A Model For the Regulation Of App Processing By Prp C -A Feementioning
confidence: 78%